Implementasi Nilai-Nilai Ajaran Islam untuk Membiasakan Akhlakul Karimah Siswa pada Pembelajaran Pendidikan Agama Islam di SD N 03 Pakan Labuah Bukittinggi - Jelly Dirma Yetti; Alimir Alimir (Lembaga Yasin AlSys, 2026)
Although the implementation of Islamic teaching values in Islamic Education (PAI) learning is an important aspect of fostering students’ akhlakul karimah, studies that specifically discuss its implementation practices in the context of learning in elementary schools remain limited. This study aims to explore and describe the implementation of Islamic teaching values in habituating students’ akhlakul karimah in PAI learning in Grade V at SD N 03 Pakan Labuah Bukittinggi. This study used a qualitative approach with a case study design, involving participants consisting of the PAI teacher, the principal, and students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using descriptive qualitative analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that the implementation of Islamic teaching values was carried out in an integrated manner through learning activities, habituation of worship, and teacher exemplarity, which had an impact on improving students’ akhlakul karimah behavior, such as discipline, politeness, and worship habits, although there were still variations in the consistency of students’ behavior. These findings contribute to strengthening Islamic education and character education based on habituation and exemplarity, while also expanding understanding of the implementation of Islamic teaching values at the elementary school level. The conclusion of the study emphasizes the importance of the role of teachers and school culture in shaping students’ morals, as well as the need for synergy with families as support for sustainable habituation.